2021
DOI: 10.1002/rrq.383
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Play Experiences in Early Literacy: Expanding the Science of Reading

Abstract: Children's experiences in preschool and kindergarten influence their future literacy learning. Although emergent literacy has traditionally been supported by play-based experiences, there has been a decline in play opportunities in recent years. Media publications citing the science of reading have called for more focus on systematic, direct instruction of skills in phonics and phonemic awareness. However, from the perspective of the simple view of reading, the process of learning to read involves developing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
1
15
0
3
Order By: Relevance
“…Understanding the function of texts is an important component of emergent writing (Owocki, 1999); likewise, understanding the relationship between genre and form is a critical aspect of reading across students' academic trajectories (Hornof, 2008). These examples reinforce our theoretical understanding of how play and early literacy are interrelated and complementary (Rand & Morrow, 2021).…”
Section: Figure 2 Fruit Salad Recipementioning
confidence: 97%
“…Understanding the function of texts is an important component of emergent writing (Owocki, 1999); likewise, understanding the relationship between genre and form is a critical aspect of reading across students' academic trajectories (Hornof, 2008). These examples reinforce our theoretical understanding of how play and early literacy are interrelated and complementary (Rand & Morrow, 2021).…”
Section: Figure 2 Fruit Salad Recipementioning
confidence: 97%
“…Without mediation, play can simply reinscribe existing societal disparities through inclusion, exclusion, bullying, or limited access to materials (Wood, 2014). Play research has found teachers want clear guidance for mediating play and integrating literacy effectively (Neaum, 2020;Pyle et al, 2018;Rand & Morrow, 2021). Portier et al (2019) offer helpful K-2 teacher mediation strategies for literacy play curricular activities.…”
Section: A Framework For Integrating Play and Literacymentioning
confidence: 99%
“…Over the last two decades, space for unstructured, spontaneous, child‐directed play has been squeezed out of many classrooms. Furthermore, children in affluent, well‐resourced schools are more likely to have access to curricular play periods than children in under‐resourced, highly monitored schools where high‐stakes testing determines the classroom schedule (Rand & Morrow, 2021). Once an unquestioned staple of the early childhood curriculum, play has become an optional, nice‐if‐we‐have‐the‐time activity that is all but extinct in first grade, vanishing in kindergarten, and endangered in preschool (Bassok et al, 2016; Christakis, 2016).…”
Section: Bringing Play (Back) To Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the critical aspect of learning through play has been seen as a social experience. In essence, when child learned through play, literacy can be achieved through such a literacy, considering that the learning environment could be stronger and more desirable for them to prosper (Rand & Morro, 2021;Moore, 2020;Chopra & Khanna, 2019;Moyles, 2005;Arce (2000) reported that play offer strong chance for children to learn. Also, play enable teachers to better understand the best way to set up and manage a classroom which will make it more conducive and easier for children to play and learn skills (Dewar, 2017).…”
Section: Play and Literacy Skillsmentioning
confidence: 99%